Teletandem e episódios relacionados a cultura - Telles, João Antonio [UNESP]; Zakir, Maisa de Alcântara [UNESP]; Funo, Ludmila Belotti Andreu [UNESP] (FapUNIFESP (SciELO), 2015)
Teletandem is a telecollaborative learning context that involves pairs of native (or competent) speakers of different languages. Using Skype, each participant plays the role of learner for half an hour by speaking and practicing the language of his partner. This paper focuses on a teletandem interaction between two university students - one Brazilian and one American. In the first part, we sustain our proposition that the teletandem participants share information regarding the respective cultures. In the second part, we present five dimensions of the concept of culture, defi ne cultural learning and propose a unit of analysis for interpreting the data - the culture-related episode. Finally, we suggest guidelines for further research related to the learning of languages and cultures in online collaborative contexts.
Teletandem and culture-related episodes
Keywords: Cultural learning; Culturerelated episode; Language learning; Teletandem